2016
DOI: 10.1093/intqhc/mzw028
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of US Department of veterans affairs mental health clinician perspectives on patient-centered care

Abstract: If patient-centered care is to be practiced fully in mental health settings, healthcare institutions need to develop multimodal strategies to enhance clinician-clinician and clinician-patient collaborations to promote and support a focus on discovery and shared accountability for outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Patient-centered care is often characterized by shared patient-clinician power and responsibility, a biopsychosocial orientation, patient and clinician humanity, and a therapeutic alliance [20]. True patient-centered care has been thought to be difficult to implement in mental health settings, where clinicians historically have had role expectations in which the patient is viewed as someone to “protect” and for whom the clinician is “responsible” [21-23]. We saw similar themes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-centered care is often characterized by shared patient-clinician power and responsibility, a biopsychosocial orientation, patient and clinician humanity, and a therapeutic alliance [20]. True patient-centered care has been thought to be difficult to implement in mental health settings, where clinicians historically have had role expectations in which the patient is viewed as someone to “protect” and for whom the clinician is “responsible” [21-23]. We saw similar themes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar barriers in implementing patient-centered outcomes in nephrology and other medical specialties have been previously identified, including rigid regulatory structures, disease-centric incentivization schemes on the basis of laboratory parameters (e.g., Kt/V and hemoglobin), resource constraints, emphasis on biochemical targets and technical procedures, and lack of mechanisms for patients to communicate their priorities (10,(43)(44)(45)(46). A study in mental health professionals also found that clinicians were concerned about being held accountable for managing the array of needs and goals that a patient may have (47). Our findings add to existing literature by highlighting some of the unique challenges in the context of hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…A 5-year postimplementation study of the MLMS project showed that a majority of providers found reading life stories a valuable use of clinical time and helped them provide more personalized, patient-centered care ( 3 ). Acknowledging the patient as a holistic individual empowers that patient to play an active role in their care ( 4 6 ) and has been shown to improve patient experience, patient-provider trust, and health outcomes ( 5 , 7 9 ).…”
Section: Introductionmentioning
confidence: 99%